Age and Human Regenerative Capacity Impact of Cardiovascular Risk Factors. Issue 7 (16th September 2016) - Al Mheid, Ibhar; Hayek, Salim S.; Ko, Yi-An; Akbik, Faysal; Li, Qunna; Ghasemzadeh, Nima; Martin, Greg S.; Long, Qi; Hammadah, Muhammad; Maziar Zafari, A.; Vaccarino, Viola; Waller, Edmund K.; et al.
Abstract : Rationale: : We investigated aging of human endogenous reparative capacity and aimed to clarify whether it is affected by presence of cardiovascular disease or its risk factors (RFs). Objective: : Circulating progenitor cell (PC) levels reflect endogenous regenerative potential. The effect on PC of healthy aging compared with aging with RFs or cardiovascular disease (CVD) is unknown. We examined whether exposure to RF and CVD leads to an accelerated decline in circulating PC with increasing age. Methods and Results: : In 2792 adult subjects, 498 were free of RFs (smoking, diabetes mellitus, hypertension, or hyperlipidemia), 1036 subjects had 1 to 2 RF, and 1253 had ≥3 RFs or CVD. PC were enumerated by flow cytometry as CD45 med+ mononuclear cells expressing CD34 and subsets coexpressing CD133, CXCR4, and vascular endothelial growth factor receptor-2 epitopes. Younger age, male sex, and larger body size correlated with higher PC counts ( P <0.01). After multivariable adjustment, both age and RF categories were independently associated with PC counts ( P <0.05), with lower PC counts in older subjects and those with higher RF burden or CVD. PC counts remained unchanged with increasing age in healthy individuals. There were significant interactions between age and RF categories ( P ⩽0.005), such that for younger subjects (<40 years), RFs were associated with increased PC counts, whereas for older subjects (>60 years), RFs and CVD were associated with lower PC counts. Conclusions: : Circulating PC levels do not decline with healthy aging; RF exposure at a younger age stimulates PC mobilization, whereas continued exposure is associated with lower PC levels in later life. Over the lifespan, exposure to RFs and CVD is associated with an initial stimulation and subsequent decline in circulating PC levels, which reflect endogenous regenerative capacity. Abstract : Supplemental Digital Content is available in the text.